2015
DOI: 10.18203/2394-6040.ijcmph20150480
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to environmental tobacco smoke among non-smoker adult females in urban households of Aligarh, India

Abstract: Background: Environmental tobacco smoke is a serious global public health problem. A better understanding of the correlates of Environmental tobacco smoke exposure could guide the development of evidence based Environmental tobacco smoke exposure reduction interventions. The study is conducted with the objective to describe the pattern of and factors associated with Environmental tobacco smoke exposure among non-smoking adult females in urban areas of Aligarh, Uttar Pradesh, India. Methods: A total of 439 hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 9 publications
(11 reference statements)
3
4
0
Order By: Relevance
“…The present findings revealed that the highest degree of ETS occurred respectively at home, public places and the workplace which was consistent with the findings reported by Ahmed [11] , Palipudi [5] and Al Zabadi et al [2] that found the highest degree of ETS to occur at home. Some other investigations reported similar findings too [15,16] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present findings revealed that the highest degree of ETS occurred respectively at home, public places and the workplace which was consistent with the findings reported by Ahmed [11] , Palipudi [5] and Al Zabadi et al [2] that found the highest degree of ETS to occur at home. Some other investigations reported similar findings too [15,16] .…”
Section: Discussionsupporting
confidence: 92%
“…The findings reported by Gilman et al revealed that men smoked much more than women and this exposed women inadvertently to tobacco smoke produced by men [12] . A body of related literature reported similar findings [7,11,13,14] . Unlike the present Study, Skorge et al [13] and Kaneita et al [14] observed that men were more exposed to tobacco smoke than women.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations